ANALISI PERCAKAPAN MELALUI TELEPON ORANG JEPANG DAN ORANG INDONESIA: STUDI KASUS DALAM MEMBUAT JANJI BERTEMU - Muhammad Robby Masyfa; Arza Aibonotika; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study discusses the functions that appear in Japanese conversations in making appointments on the telephone. The method used in this study is a qualitative descriptive method. The source of the data in this study is in the form of Japanese telephone conversations recorded using zoom media. The number of respondents in this study consisted of 10 students at Kobe University Japan which will be divided into two groups of Japanese people who will have telephone conversations in making appointments with close friends and with people of higher social status. The data analysis technique used qualitative analysis. The results of data analysis obtained in this study are the functions that appear in Japanese conversations when making telephone appointments with close friends or peers (students and students) and with people with higher social status (lecturers and students).Key Words: Discourse Analysis, Communication, Pragmatics